Challenges and Opportunities in Cross-Cultural Family Research: A Critical Reflection - Eslami, Fereydon; Hooshmandi , Roodabeh (Journal of Psychosociological Research in Family and Culture, 2024)
This article aims to present a critical reflection on the challenges and opportunities in cross-cultural family research. This reflection is informed by a comprehensive review of the literature on cross-cultural research, encompassing various disciplines such as psychology, sociology, and nursing. The complexities of conducting cross-cultural family research are evident in the diverse array of challenges identified in the literature, including methodological, ethical, and communication challenges. However, amidst these challenges, there are significant opportunities for advancing our understanding of family dynamics within diverse cultural contexts. In conclusion, the critical reflection on challenges and opportunities in cross-cultural family research reveals the intricate nature of conducting research in diverse cultural contexts. While the challenges are multifaceted, ranging from methodological and ethical considerations to communication barriers, the opportunities for advancing knowledge and understanding are equally significant. By addressing these challenges and embracing the opportunities, particularly those offered by technological advancements and interdisciplinary collaborations, researchers can contribute to a more comprehensive and culturally sensitive understanding of family dynamics across the globe. It is through such dedicated efforts that we can hope to build a more inclusive and understanding world.